2008
DOI: 10.1111/j.1540-4781.2008.00715.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Second Language Development From a Dynamic Systems Perspective

Abstract: This article illustrates that studying intra‐individual variability in Second Language Development can provide insight into the developmental dynamics of second language (L2) learners. Adopting a Dynamic Systems Theory framework (Thelen & Smith, 1994; van Geert, 1994) and using insights from microgenetic variability studies in developmental psychology (Siegler, 2006), we focus on L2 systems during a time of rapid development, applying advanced visualization techniques. A reinterpretation of a longitudinal stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
199
2
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 278 publications
(211 citation statements)
references
References 27 publications
6
199
2
4
Order By: Relevance
“…This is not to say that we need to explain every single instance of a deviation from a general pattern. As in other areas of language development, variation is a reflection of the developmental process resulting from the interaction of many internal variables that cannot be taken apart to study the impact of each individual factor (van Dijk & van Geert, 2005;Verspoor et al, 2008). Studies of gestures and language development will have to be methodologically creative to find ways of taking variation into account.…”
Section: Variation and Individual Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not to say that we need to explain every single instance of a deviation from a general pattern. As in other areas of language development, variation is a reflection of the developmental process resulting from the interaction of many internal variables that cannot be taken apart to study the impact of each individual factor (van Dijk & van Geert, 2005;Verspoor et al, 2008). Studies of gestures and language development will have to be methodologically creative to find ways of taking variation into account.…”
Section: Variation and Individual Differencesmentioning
confidence: 99%
“…In SLD the effect of a range of psychosocial factors have been explored, such as intelligence, language aptitude, memory capacity, attitudes, motivation, personality traits, and cognitive style (e.g. de Bot et al, 2005: 65-75;Dörnyei, 2006;Verspoor, Lowie, & van Dijk, 2008). For instance, intelligence matters more in tutored than in untutored SLD, and more in grammar learning than in other skills.…”
Section: Variation and Individual Differencesmentioning
confidence: 99%
“…Increasing complexity at some point in the system (e.g., inflection or clause length) may also interact with developing complexity at other points in the system (e.g., subordination or global narrative skills), either in supportive or in competing ways (cf. Berman 2016; Verspoor et al 2008). Children thus acquire increasingly more tightly cohesive syntactic packaging abilities (Berman 2016: 475ff;cf.…”
Section: Gradual Development At the Local Complexity Levelmentioning
confidence: 99%
“…Structural complexity can be measured in terms of phrase, clause, utterance, or turn length (e.g., Hsu 2017: 12-13;Pallotti 2015: 123-124;Verspoor et al 2008; see Bhat and Yoon 2015: 46 for an overview), degrees of irregularity (cf. Culicover 2014: 148-149), and/or levels of hierarchical structure (e.g., mean number of modifiers per noun phrase or mean number of higher level constituents per sentence, controlling for number of words, cf.…”
Section: Gradual Development At the Global Complexity Levelmentioning
confidence: 99%
“…Thus, concurrent attention to different areas of L2 is considered difficult. Verspoor, Lowie, and van Dijk (2008) conducted a longitudinal study (over a period of 3 years) observing the academic writing of an advanced learner of English. The researchers reported that the sentence length measure and the type token ratio did not develop concurrently and that there was a competitive relationship between them, pointing to an absence of the ability to allocate attentional resources equally on the part of the language learner.…”
Section: Literature Reviewmentioning
confidence: 99%